PENGARUH MEDIA DOUBLE BOX TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA ANAK USIA 5-6 TAHUN DI TK BINA KASIH DESA BATU BELAH KECAMATAN KAMPAR KABUPATEN KAMPAR - Melya Nopri Sastra; Rita Kurnia; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of field observations on the ability to read the beginning of students has not developed optimally. So it is necessary to apply the Double Box media. The purpose of this study was to examine the effect of using Double Box media on the ability to read the beginning of children aged 5-6 years. This research was conducted at tk bina kasih batu belah village, kampar sub-district, kampar district during July 2018 to March 2019 for observation and research. The research used experimental method with one group pre-test post-test design with 15 samples. The data collection technique used in this research is using observation sheet the ability to read the beginning of student. Data anlisis technique using t-test by using SPSS program ver 20. From result of data analysis obtained tcount equal to 36,047 bigger than t table = 2,145 with sig 0.000 <0.05. It can be concluded that there are differences in the ability to read the beginning significantly before and after the application of the Double Box media. Based on hypothesis test results obtained there is the effect of use Double Box media to the ability to read the beginning of children aged 5-6 years in tk bina kasih batu belah village, kampar sub-district, kampar district of 67,27% .Key Words: Double Box, Ability to Read the Beginning